Initial management of acute ischaemic stroke. (2nd January 2021) - Appleton, Jason P; Mullhi, Randeep; Singh, Naginder
Abstract : The management of acute ischaemic stroke has been revolutionised by effective reperfusion therapies including thrombolysis and mechanical thrombectomy. In particular, mechanical thrombectomy has heralded a new era in stroke medicine. There have also been developments to improve clinical outcomes for patients who have had an acute ischaemic stroke but are not eligible for this procedure. This article presents an update on the initial management of acute ischaemic stroke, including reperfusion therapies, periprocedural considerations and ongoing research for potential improvements in the care of these patients.